Molecular Docking Study on Interaction of Polyvinyl Alcohol (PVA) with Group IA Bacteriocin - Ünlü, Nihan; Özgen, Arzu; Canbay, Canan Aksu (My University, 2023)
PVA with the molecular formula (C2H4O)n is a polymer prepared from polyvinyl acetates by replacing acetate groups with hydroxyl groups. It is a synthetic polymer with low surface tension, flexible and soft, water-soluble and cross-linkable thanks to the hydroxyl groups in its structure, biodegradable and non-toxic due to the carbon bonds in its chain. Bacteriocins are compounds of a protein nature that are ribosomally synthesized by bacteria and suitable for use as a filler in polymer matrices, especially in food packaging systems, and drug design because they are natural antimicrobial compounds sensitive to various enzymes and do not disrupt the physicochemical structure of foods while inhibiting pathogenic microorganisms. Considering their biochemical properties, they are generally divided into 4 different classes. The fact that Nisin and PVA have a structure that can serve a common purpose and have superior properties made us wonder about the interaction and bonding modes between these two. Molecular docking work is important because it prevents time, energy, and economic consumption and prepares the ground for the synthesis of new and advanced materials that are likely to be obtained in the laboratory environment. Therefore, in this study, Nisin bacteriocin (in Group IA) was chosen as the target, and a single monomer of the PVA polymer was chosen as the ligand, and the interaction between them was simulated by molecular docking method. A rational depiction of ligand-protein binding interactions was made.
Keywords: Nisin; molecular docking; polyvinyl alcohol